Frontline health workers and exclusive breastfeeding guidelines in an HIV endemic South African community: a qualitative exploration of policy translation - Nieuwoudt, Sara; Manderson, Lenore (BioMed Central, 2018)
Background: Mothers rely heavily on health worker advice to make infant feeding decisions. Confusing or misleading advice can lead to suboptimal feeding practices. From 2001, HIV positive mothers in South Africa were counseled to choose either exclusive breastfeeding or exclusive formula feeding to minimize vertical HIV transmission. On the basis of revised World Health Organization guidelines, the government amended this policy in 2011, by promoting exclusive breastfeeding and discontinuing the provision of free formula. We explored how health workers experienced this new policy in an HIV endemic community in 2015–16, with attention to their knowledge of the policy, counselling practices, and observations of any changes. Methods: We interviewed eleven health workers, from four community health clinics, who had counseled mothers before and after the policy change. The transcribed interviews were analyzed thematically, using a hybrid coding approach. Results: The scientific rationale of the policy was not explained to most health workers, who mostly thought that the discontinuation of the formula program was cost-related. The content of their counseling reflected knowledge about promoting breastfeeding for all women, and accordingly they mentioned the nutritional and developmental benefits of breastfeeding. The importance of exclusive breastfeeding for all infants was not emphasized, instead counseling focused on HIV prevention, even for uninfected mothers. The health workers noted an increased incidence of breastfeeding, but some worried that to avoid HIV disclosure, HIV positive mothers were mixed feeding rather than exclusively breastfeeding. Conclusions: Causal links between the policy, counseling content and feeding practices were unclear. Some participants believed that breastfeeding practices were driven by finance or family pressures rather than the health information they provided. Health workers generally lacked training on the policy’s evidence base, particularly the health benefits of exclusive breastfeeding for non-exposed infants. They wanted clarity on their counseling role, based on individual risk or to promote exclusive breastfeeding as a single option. If the latter, they needed training on how to assist mothers with community-based barriers. Infant feeding messages from health workers are likely to remain confusing until their uncertainties are addressed. Their insights should inform future guideline development as key actors.
Keywords: Exclusive breastfeeding; Breastfeeding promotion; Health workers; Policy analysis; Qualitative research; South Africa; SDG-3: Good health and well-being